2017
DOI: 10.1002/cncr.31106
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer outcomes for men aged younger than 65 years with Medicaid versus private insurance

Abstract: Racial disparities in the outcomes of patients with CaP were observed in privately insured cohorts, whereas these disparities appeared to be reduced among patients with Medicaid insurance. However, outcomes need to be improved overall. Whether the equality in outcomes for Medicaid is due to white and African American patients doing "equally poorly" or "equally well" is unclear. Cancer 2018;124:752-9. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Studies have shown that the disparities in cancer outcomes in patients with prostate cancer (and other cancers) diminish after US patients become eligible for Medicare . Furthermore, among patients with PC, there are no apparent disparities by race noted for men with Medicaid insurance . Finally, when AA men receive care as part of randomized controlled trials, they appear to achieve outcomes that are as favorable if not better than those of their NHW counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that the disparities in cancer outcomes in patients with prostate cancer (and other cancers) diminish after US patients become eligible for Medicare . Furthermore, among patients with PC, there are no apparent disparities by race noted for men with Medicaid insurance . Finally, when AA men receive care as part of randomized controlled trials, they appear to achieve outcomes that are as favorable if not better than those of their NHW counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Furthermore, among patients with PC, there are no apparent disparities by race noted for men with Medicaid insurance. 12 Finally, when AA men receive care as part of randomized controlled trials, they appear to achieve outcomes that are as favorable if not better than those of their NHW counterparts. For example, in the Prostate Cancer Intervention Versus Observation Trial (PIVOT), there was no difference in outcome noted by race and no difference in the benefit of prostatectomy on PCSM between AA and NHW men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is evidence that Medicaid increases overall health care access for low‐income individuals, state measures such as increased out‐of‐pocket costs and restrictions on specialist care may subdue the benefits of Medicaid coverage for a financially burdensome disease such as bladder cancer . It has in fact been shown for other cost‐intensive cancers (eg, colorectal cancer and head and neck cancer) that Medicaid coverage, compared with private insurance, is associated with poorer long‐term outcomes that are similar to those of the uninsured . In addition, many of the previously documented insurance‐based health disparities have been demonstrated in screening‐detectable cancers (eg, breast cancer, prostate cancer, and colorectal cancer) .…”
Section: Discussionmentioning
confidence: 99%